Reprograming the tumor immunologic microenvironment using neoadjuvant chemotherapy in osteosarcoma - Deng, Chuangzhong; Xu, Yanyang; Fu, Jianchang; Zhu, Xiaojun; Chen, Hongmin; Xu, Huaiyuan; Wang, Gaoyuan; Song, Yijiang; Song, Guohui; Lu, Jinchang; Liu, Ranyi; Tang, Qinglian; et al. (Cancer science, 2020)
Tumor‐infiltrating immune cells play a crucial role in tumor progression and response to treatment. However, the limited studies on infiltrating immune cells have shown inconsistent and even controversial results for osteosarcoma (OS). In addition, the dynamic changes of infiltrating immune cells after neoadjuvant chemotherapy are largely unknown. We downloaded the RNA expression matrix and clinical information of 80 OS patients from the TARGET database. CIBERSORT was used to evaluate the proportion of 22 immune cell types in patients based on gene expression data. M2 macrophages were found to be the most abundant immune cell type and were associated with improved survival in OS. Another cohort of pretreated OS samples was evaluated by immunohistochemistry to validate the results from CIBERSORT analysis. Matched biopsy and surgical samples from 27 patients were collected to investigate the dynamic change of immune cells and factors before and after neoadjuvant chemotherapy. Neoadjuvant chemotherapy was associated with increased densities of CD3+ T cells, CD8+ T cells, Ki67 + CD8+ T cells and PD‐L1+ immune cells. Moreover, HLA‐DR‐CD33+ myeloid‐derived suppressive cells (MDSC) were decreased after treatment. We determined that the application of chemotherapy may activate the local immune status and convert OS into an immune “hot” tumor. These findings provide rationale for investigating the schedule of immunotherapy treatment in OS patients in future clinical trials. Host anti–tumor immune response boosted by neoadjuvant chemotherapy. Following neoadjuvant chemotherapy, CD3+ T cells increased significantly and there was a trend of increased cytotoxic T cells. CD8+ T cells in both tumor center and stroma also increased remarkably. Importantly, activated CD8+ T cells, defined as Ki67 + CD8+ T cells, were more abundant in post–chemotherapy samples, and were negatively correlated with the proliferation ability of tumor cells.